Corporate Co-Agglomeration and Green Economy Efficiency in China - Zhu, Xiaoyan; Zhang, Yunqi; Yang, Weizhi (Frontiers in Psychology, 2022)
The paper empirically studies the effect of co-agglomeration of corporates in manufacturing and producer services on green economy efficiency in China by using the methods of panel OLS, IV and two-step system GMM. The panel data of 27 provinces in China from 2000-2019 were collected to calculate the green economy efficiency and the level of co-agglomeration. We find that co-agglomeration of corporates in manufacturing and producer services contributes to regional green economy efficiency, and there is an inverted u-shaped relationship between them. Variables such as human capital, foreign direct investment, science and technology innovation capacity and environmental regulations performs a elevating effect on green economy efficiency while local fiscal expenditure on environmental protection has no effect . Therefore, the main countmeasures of this paper are: (1) The co-agglomeration of corporates in manufacturing and producer services should be effectively accelerated, but the focus is on improving industrial synergy rather than just increasing concentration geographically; (2) Infrastructure and regulations should be improved to create a favorable market competitive environment and the structure of foreign direct investment should be controled within a proper range et al.